Deschooling: A Movement Towards Educational Transformation - Upadhyay, Arati Upadhyay; Pandey, Yogendra Pandey (THE PRIMARY TEACHER, 2018)
Children learn the most important lessons of their lives from their homes and community. Schooling provides literacy and knowledge beyond the society that the child may be present in; however, a lot may be imbibed from parents and elders who may never have had schooling, yet have learnt from the school of experience. Deschooling as a concept is new and is emerging for people that can be better utilised to impart formal education to children. This form of education was majorly about building a skill set rather than following a routine existence from the bookish curriculum. This paper is an attempt towards discussing how deschooling if practised properly can prove to be a transformative way of learning.